Changes in the Use of Fuel Oil Into Electyrical Energy for Vehicles - Muchdar Daeng Patabo; Cicilia E. Angelia; Rivan M. Golioth; Matthew Waworuntu; Varrel D.P. Sunyoto (Publikasi Indonesia, 2025)
The escalating household electricity consumption presents significant challenges for energy management and sustainability, with lighting systems accounting for 20-30% of total residential energy usage. The increase in household electricity consumption is a major concern in energy efficiency. One solution that is widely recommended is the use of energy-saving lamps such as Light Emitting Diode (LED). This study aims to comprehensively analyze the impact of LED lamp adoption on household electricity savings by comparing energy consumption, cost efficiency, and environmental benefits across different lighting technologies including incandescent, fluorescent, and LED lamps. This study aims to analyze the effect of LED lamp use on electricity savings in households. The research methodology employs an experimental quantitative approach involving five urban households, each utilizing 10 lighting units under controlled conditions. The study compares 60-watt incandescent lamps with 10-watt LED lamps over a 30-day period, with standardized usage patterns of 6 hours daily operation. Data collection includes power consumption measurements, electricity cost calculations based on prevailing tariffs (IDR 1,500 per kWh), and comparative analysis of long-term cost-benefit ratios including lamp lifespan and replacement frequencies. The results of the study showed that LED lamps were able to save energy up to 80% compared to incandescent lamps and 50% compared to fluorescent lamps. The implications of this research support the transition to LED lighting technology as an effective strategy for household energy management, contributing to reduced electricity bills, lower carbon emissions, and sustainable energy consumption patterns that benefit both individual households and national energy security objectives.